Comparison of Patent Foramen Ovale Sizing by Transesophageal Echocardiography and Balloon Sizing in Patients Undergoing Percutaneous Closure - Birgitte Carbuhn Larsen, MD; Martin Christian Harmsen, MD; Henrik Vase, MD, PhD; Jens Erik Nielsen-Kudsk, MD, DMSc; Asger Andersen, MD, PhD (Structural Heart)
Background: A patent foramen ovale (PFO) has a complex anatomy, and evaluating the size before closure may be challenging. We aimed to investigate the correlation between preprocedural transesophageal echocardiography (TEE) and balloon sizing of PFO in patients undergoing percutaneous PFO closure. Methods: A retrospective single-center study with analysis of 100 patients who, due to paradox thromboembolism in the left circulation, underwent percutaneous PFO closure. The PFO sizing was compared to measures attained by TEE and balloon sizing using linear regression analysis. Results: PFO size measured by TEE occurred smaller than balloon sizing (2.19 mm [95% CI: 1.91 to 2.46] vs. 8.51 mm [95% CI: 8.02 to 9.00], p < 0.001). Additionally, neither the PFO channel length nor the atrial septal mobility measured by TEE correlated to the PFO size attained by balloon sizing, respectively (slope −0.018 [95% CI: −0.117 to 0.081], R = 0.036, p = 0.719) and (slope 0.049 [95% CI: ?0.043 to 0.141], R = 0.105, p = 0.297). Statistically significant difference in regression analysis but poor correlation was found between both TEE attained PFO and shunt size when compared to balloon sizing. Diverting patients according to the size of the PFO shunt was not statistically significant between PFO of moderate size compared, respectively, to a large and small PFO size. However, a difference was observed between a small and large PFO shunt size. Conclusions: PFO defect and shunt size measured by TEE showed a poor correlation with balloon sizing. Neither PFO channel length nor septal mobility were correlated to the PFO size measured by balloon sizing.